Revelando os Brasis: o projeto - Calabre, Lia (Políticas Culturais em Revista, 2012)
O artigo tem por objetivo analisar o Projeto Revelando os Brasis em suas duas primeiras edições (2004 e 2005). O estudo resgata parte da história do projeto e busca compreender seu papel tanto no campo da experimentação da produção audiovisual como no da democracia cultural. PALAVRAS-CHAVE: Revelando os Brasis. Audiovisual. Política cultural.Revealing the different Brazils: the projectABSTRACT: The article aims at analyzing the project Revealing the different Brazils, especially its two first editions (2004 and 2005). The study recovers the project's history and tries to understand its role, both in the field of audiovisual production experimentation and in that of cultural democracy. KEYWORDS: Revealing the different Brazils. Audiovisual. Cultural policy.